2020
DOI: 10.1080/10408398.2020.1835820
|View full text |Cite
|
Sign up to set email alerts
|

Phytosterols and phytostanols and the hallmarks of cancer in model organisms: A systematic review and meta-analysis

Abstract: Phytosterols and phytostanols are natural products present in vegetable oils, nuts, and seeds, or added to consumer food products whose intake is inversely associated with incidence and prognosis of several cancers. Randomized cancer prevention trials in humans are unfeasible due to time and cost yet the cellular processes and signaling cascades that underpin anti-cancer effects of these phytochemicals have been explored extensively in vitro and in preclinical in vivo models. Here we have performed an original… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…Furthermore, of the studies that reported randomisation of groups, none reported their method of randomisation. Additionally, no studies reported rationale behind the size of study groups, with this issue noted in previous meta-analyses on pre-clinical models of cancer [33, 76]. Comparably, studies assessing CE content in tissue exhibited poorer reporting on our risk of bias survey (Fig8B), however this is likely due to the papers within this cohort being considerably older (average publication date = 1986) than those assessing SOAT interventions in pre-clinical models (average publication date = 2018).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, of the studies that reported randomisation of groups, none reported their method of randomisation. Additionally, no studies reported rationale behind the size of study groups, with this issue noted in previous meta-analyses on pre-clinical models of cancer [33, 76]. Comparably, studies assessing CE content in tissue exhibited poorer reporting on our risk of bias survey (Fig8B), however this is likely due to the papers within this cohort being considerably older (average publication date = 1986) than those assessing SOAT interventions in pre-clinical models (average publication date = 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The World Cancer Research Fund (WCRF) remain unable definitively to include or exclude cholesterol in the aetiology of cancer [88], even now, more than 20 years after the International Agency for Research on Cancer (IARC) indicated that evidence is inadequate [89]. Drugs and dietary factors that reduce cholesterol levels also reduce the risk of developing and/or dying from cancer in some situations [9092]. Cholesterol is widely utilised, both structurally in the plasma membrane, and as a precursor for an array of hormones, steroids, and vitamins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nutritional and epidemiological studies indicate that cholesterol metabolism may play a role in the aetiology and severity of TNBC [3][4][5][6]. The liver x receptors (LXRα/NR1H3; LXRβ/NR1H2) are homeostatic regulators of cholesterol metabolism and as such have been suggested as potential therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%